 ×     #### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
```
if a(y+z)=x , b(z+x)=y , c(x+y)=z prove that x^2/a(1-bc)=y^2/b(1-ca)=z^2/c(1-ab)
if a(y+z)=x , b(z+x)=y , c(x+y)=z prove that x^2/a(1-bc)=y^2/b(1-ca)=z^2/c(1-ab)

```
2 years ago

```							A(y+z)=b(z+x)=c(x+y) Assume n= a(y+z)=b(z+x)=c(x+y) n=a(y+z) ,n= b(z+x) , n= c(x+y) y+z = (n/a).....................(1) z+x = (n/b).....................(2) x+y = (n/c).....................(3) subtracting (2) - (1) , (3) - (2) , (1) - (3) we get x - y = n( a - b )/ab ..................(4) y - z = n ( b - c )/bc...................(5) z - x = n( c - a )/ac...................(6) x-y/c(a-b) = [ n ( a - b )/ab ] / c( a - b ) = n/abc y-z/a(b-c) = [ n ( b - c )/bc ] / a( b - c ) = n/abc z-x/b(c-a) = [ n ( c - a )/ac ] / b( c - a ) = n/abc y-z/a(b-c)=z-x/b(c-a)=x-y/c(a-b) alsox^2/a(1-bc)=y^2/b(1-ca)=z^2/c(1-ab)
```
2 years ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions